Cross-sectional study on the association between the fibrosis-4 index and co-occurring myocardial infarction in Chinese patients with type 2 diabetes mellitus - Sun, Ziyi; Zhang, Jin; Duan, Jinlong; Wang, Qingqing; Yun, Zhangjun; Lin, Jianguo; Yang, Yuhan; Zuo, WenXi; Wang, Zeqi; Xiong, Xingjiang; Yao, Kuiwu (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies indicated that the Fibrosis-4 Index (FIB-4), an evaluation metric for liver fibrosis, is associated with adverse outcomes in coronary artery disease. However, the correlation between FIB-4 and myocardial infarction (MI) in Chinese patients with Type 2 Diabetes Mellitus (T2DM) has not been well-defined. Thus, this study aims to elucidate the association between FIB-4 and MI in Chinese T2DM patients.MethodsCross-sectional data were collected from T2DM patients at two hospitals in China, designated as the discovery and validation centers. The exposure variable, FIB-4 index, was derived from patient age, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and platelet count. This index was stratified into four distinct clusters via k-means clustering analysis. The primary outcome was defined as the incidence of co-occurring MI. Logistic and restricted cubic spline regression was conducted to assess the association between the FIB-4 index and MI in Chinese T2DM patients.ResultsIn the discovery phase, data were analyzed from 2,980 T2DM patients, including 1,114 females (37.38%), with 58 years average age (SD: 10.4). Among them, 190 were also MI patients. Based on the fully adjusted logistic regression analysis, the odds ratio (OR) for the second cluster was 1.00 (95% CI, 0.60-1.40); for the third cluster, it was 1.94 (95% CI, 1.32-2.57), and for the poorest controlled cluster it was 16.18 (95% CI, 14.97-17.39) in comparison to the best-controlled cluster of FIB-4. Restricted cubic spline regression revealed a linear relationship between the FIB-4 index and MI risk. Subgroup analysis demonstrated that this association was significant in elderly adults, females with high BMI, and those with comorbidities such as hypertension, coronary artery disease, and chronic heart failure. These findings yield consistent results in the validation set (n = 224).ConclusionsAmong Chinese patients with T2DM, elevated FIB-4 levels have been independently associated with MI, particularly among females and individuals with concomitant hypertension. Consequently, the FIB-4 index is anticipated to serve as a promising tool for early detection and risk stratification in this population.